2019
DOI: 10.26444/aaem/109974
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution: how many cigarettes does each Pole ‘smoke’ every year and how does it influence health, with special respect to lung cancer?

Abstract: Introduction. Air pollution is one of the most important issues of our times. Air quality assessment is based on the measurement of the concentration of substances formed during the combustion process and micro-particles suspended in the air in the form of an aerosol. Microscopic atmospheric particulate matters (PM) 2.5 and 10 are mixtures of organic and inorganic pollutants smaller than 2.5 and 10 µm, respectively. They are the main cause of negative phenomena in the earth's atmosphere of Earth and human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For environmental monitoring applications, NO 2 is more relevant. NO 2 is not only a strong oxidizing agent and air pollutant but also reacts in the atmosphere to form ozone (O 3 ) and acid rain. , Continuous NO 2 exposure may cause respiratory diseases, ,,, but it cannot be detected by the human senses. Ideally, NO 2 gas sensors should detect NO 2 in the presence of other interfering gas species and should enable detection in explosive environments, i.e., in the presence of combustible materials without further modification (intrinsically safe).…”
Section: Introductionmentioning
confidence: 99%
“…For environmental monitoring applications, NO 2 is more relevant. NO 2 is not only a strong oxidizing agent and air pollutant but also reacts in the atmosphere to form ozone (O 3 ) and acid rain. , Continuous NO 2 exposure may cause respiratory diseases, ,,, but it cannot be detected by the human senses. Ideally, NO 2 gas sensors should detect NO 2 in the presence of other interfering gas species and should enable detection in explosive environments, i.e., in the presence of combustible materials without further modification (intrinsically safe).…”
Section: Introductionmentioning
confidence: 99%
“…Several particles present in polluted air, including PM2.5, PM10, and NO 2 , are considered to be carcinogenic, with an emphasis on lung cancer development [58]. Badyda et al revealed that in 11 large Polish cities between 2006 and 2011, 20-40% of lung cancer was associated with chronic exposure to PM2.5 [59].…”
Section: Own Experiencementioning
confidence: 99%
“…Moreover, they estimated that in the years 2006–2011, in eleven large Polish cities, about 20% to 40% of lung cancer cases seemed to be attributable to chronic PM 2.5 exposure [ 94 ]. Chudzik et al estimate that in the years 2009–2017, on average, each Pole “smoked” an equivalent of about 10 cigarettes a day [ 95 ]. Thus, every Pole over 60 years old will reach the “30 pack-years of smoking”, which is considered a threshold for being classified as a high-risk patient and is an indication for low-dose computer tomography screening [ 95 , 96 ].…”
Section: Adultsmentioning
confidence: 99%
“…Chudzik et al estimate that in the years 2009–2017, on average, each Pole “smoked” an equivalent of about 10 cigarettes a day [ 95 ]. Thus, every Pole over 60 years old will reach the “30 pack-years of smoking”, which is considered a threshold for being classified as a high-risk patient and is an indication for low-dose computer tomography screening [ 95 , 96 ]. Therefore, ambient air pollution may be considered an independent risk factor for lung cancer in Poland [ 95 ].…”
Section: Adultsmentioning
confidence: 99%
See 1 more Smart Citation